The effect of body mass index and its interaction with family history on hypertension: a case-control study - An-le Li; Qian Peng; Yue-qin Shao; Xiang Fang; Yi-ying Zhang (BMC, 2019)
Abstract Background BMI is an indicator commonly used in the world to measure the weight and height of the body, it reflects the comprehensive outcome of acquired lifestyle; FH is a sign reflecting the main role of genetic factors. This study aimed to evaluate the effect of BMI and interaction with FH on hypertension risk in Shanghai adult population. Methods According to l:l matched pairs design, 342 cases and 342 controls were selected and investigated in this study, this study was performed in Shanghai, China. Participants received face-to-face questionnaire survey, anthropometric tests and laboratory examinations. Relevant indicators that reflect obesity including BMI and waist to hip ratio (WHR) were calculated. Multivariate logistic regression analysis was applied to explore the association between factors and hypertension risk. Interactive effect was evaluated by synergy index (SI), relative excess risk due to interaction (RERI), attributable proportion due to interaction (AP) and the percentage of the interaction between the pure factors (PAP). Results Among 684 study participants aged 28-87 years old, the differences of mean age and height between case group and control group are no significant (p > 0.05), but the differences of mean of weight, WC, HC, BMI and WHR are significant (p < 0.001). The OR of FH on hypertension is 4.986 (95%CI: 2.832~ 8.877); the OR of BMI on hypertension is respectively: low weight is 1.528 (95%CI: 0.551~ 4.239), overweight is 3.333 (95%CI: 1.678~ 6.617) and obesity is 7.312 (95%CI: 3.556~ 15.035). The OR of interaction between FH and BMI to hypertension is 12.993 (95%CI: 7.426~22.734). SI is 1.90 (95% CI: 1.48~3.78), RERI is 5.67 (95% CI: 1.66~11.88), AP is 43.87% (95% CI: 12.84~91.88%), and PAP is 47.55% (95%CI: 13.91~99.58%). FH and BMI have positive interaction on hypertension. 43.87% of hypertension exposed to both FH and BMI was attributable to the interaction of them. Conclusions FH and BMI are significant higher risks of hypertension; with the increase of BMI, the risk of hypertension will increase more. FH and BMI have positive interaction with hypertension, the interaction is greater than the sum of two independent actions.